Cecal Volvulus: A Rare Cause of Intestinal Obstruction - Carolina Solis Rojas; Ramon Vidrio Duarte; Diego Martín García Vivanco; Eduardo E. Montalvo-Javé (Case Reports in Gastroenterology, 2020)
Cecal volvulus is a rare cause of intestinal obstruction, with multifactorial etiologies. This is a case report describing a 52-year-old female with a cecal volvulus diagnosis made during the laparotomy procedure, which was treated with a right hemicolectomy with a side-to-side ileotransverse anastomosis. The aim of this report is to emphasize the importance of a diagnosis and appropriate treatment in this rare pathology in abdominal procedures. In this particular case, the patient benefited from an early surgical intervention without further complications, as well as an adequate postoperative evolution; it is important to acknowledge and consider this pathology during differential diagnosis, and not delay the treatment in patients with cecal volvulus. A critical review of the literature is included and discussed.